Analisis Kinerja Karyawan pada PT. BOLTZ Karawang - Ameliya, Liya; Rismayadi, Budi; Pertiwi, Wike (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This research aims to analyze employee performance at PT. Boltz Indonesia, the author uses a qualitative descriptive method using the Triangulation Technique. The data collection method used by the author was direct observation and interviews with 5 (five) people at PT. Boltz Indonesia in 2022 will see a decline, due to a lack of motivation to do the work optimally job plus there are problems with employees who are negligent in carrying out work such as leaving the machine while the engine is running and not checking the machine before starting to replace the machine blade. Performance is where someone has played for him in playing organizational strategy, both in achieving specific targets related to individual roles and/or by demonstrating competencies that are stated to be relevant for the organization. Keywords: Analysis; Employee Performance